Project-based learning as an instructional strategy to improve creative thinking in junior high school - Sutriana Sutriana (Science Center Group, 2025)
Background: Creative thinking is a fundamental competency in junior secondary science education, as it enables students to generate innovative solutions, interpret scientific phenomena, and engage in higher-order reasoning. Project-Based Learning (PjBL) has been widely recognized as a student-centered instructional approach that promotes inquiry, collaboration, and authentic problem solving. However, empirical evidence regarding its effectiveness in improving creative thinking within junior secondary science contexts remains limited and requires further investigation. Objective: This study aimed to examine the effectiveness of Project-Based Learning as an instructional strategy to improve creative thinking skills in junior secondary science education. Methods: A quasi-experimental design employing a pretest–posttest control group approach was conducted with 68 Grade VIII students divided into an experimental group receiving PjBL instruction and a control group receiving conventional teaching. The intervention was implemented over six weeks within environmental science topics. Creative thinking was assessed using a validated open-ended test measuring fluency, flexibility, originality, and elaboration. Data were analyzed using descriptive statistics, paired samples t-tests, independent samples t-tests, and effect size calculations. Results: The findings indicated that both groups demonstrated improvement; however, the experimental group achieved significantly higher posttest scores than the control group (p < 0.001). The mean gain of the experimental group was substantially greater than that of the control group. Effect size analysis revealed a very large practical impact of Project-Based Learning on students’ creative thinking development. Conclusion: Project-Based Learning effectively enhances creative thinking skills in junior secondary science education. The structured phases of investigation, collaboration, product creation, and reflection provide meaningful opportunities for students to generate original ideas and elaborate scientific solutions. The findings support the integration of Project-Based Learning as a strategic framework for strengthening 21st-century competencies in science classrooms.